SOURCE LANGUAGE INTERFERENCE IN STUDENT’S INDONESIAN-ENGLISH TRANSLATION - Hardiyanti, Diana; Santoso, Heri Dwi; Nugraheni, Yunita (Universitas Muhammadiyah Semarang, 2019)
Translation is a process of transfering the meaning from the source text into the target text reader. The translator competencies in source language and target language are needed in order to reproduce the closest equivalence in target text. This study aimed to determine interference in students’ Indonesian-English translation result. The study raised the question: How Indonesian, as the students’ first language, interferenced their translation in English when translating texts from Indonesian into English? To answer the question, the researchers analyzed students' mistakes in their Indonesian-English translation products. This study employed a descriptive qualitative method. The data source was 18 documents of students’ Indonesian–English translation results. The finding showed that the problems arised from interference was the diference of syntactical construction of Indonesian and English. The results showed that interference occurred because of students' lack of knowledge and awareness of the source and target languages.